NEED ANALYSIS OF ESP (ENGLISH FOR SPECIFIC PURPOSES) FOR PHYSICS STUDENTS - Sulistio, Prayogo Hadi (Eduscience : Jurnal Ilmu Pendidikan, 2016)
AbstractNeed analysis becomes the major point of ESP course design because it plays as major source of information about the studentsâ wants, needs, and lacks. This study is aimed at investigating language needs for Physics students. In order to collect the data, researchers used questionnaire which was administered to thirty students of Indraprasta PGRI University which were randomly chosen. The data was put into three categories; general needs, academic needs, and job needs. The result shows that listening to the radio and songs is the most important need and writing private letters is the least important need in term of general needs, doing presentation in front of the class becomes the most important need and taking notes in lectures is the least important need in term of academic needs, reading written or printed materials related to the job is the least important need and taking training course related to the job, writing application letter and CV and conversing with English-speaking colleagues are the most important needs in term of job needs. Â keywords: physics students, language needs and ESP(English for Specific Purposes)Â AbstrakPerlu analisis menjadi titik utama tentu saja ESP desain karena memainkan sumber sebagai utama informasi tentang siswa keinginan, kebutuhan, dan tidak memiliki. Penelitian ini bertujuan untuk menyelidiki kebutuhan bahasa untuk siswa Fisika. Dalam rangka untuk mengumpulkan data, peneliti menggunakan kuesioner yang diberikan kepada tiga puluh mahasiswa Indraprasta PGRI Universitas yang dipilih secara acak. Data itu dimasukkan ke dalam tiga kategori; kebutuhan umum, kebutuhan akademik, dan kebutuhan pekerjaan. Hasil penelitian menunjukkan bahwa mendengarkan radio dan lagu adalah kebutuhan yang paling penting dan menulis surat-surat pribadi adalah kebutuhan penting paling tidak dalam jangka kebutuhan umum, melakukan presentasi di depan kelas menjadi kebutuhan yang paling penting dan membuat catatan dalam perkuliahan adalah yang paling kebutuhan penting dalam hal kebutuhan akademik, membaca materi tertulis atau dicetak berhubungan dengan pekerjaan adalah kebutuhan paling penting dan mengambil kursus pelatihan yang berkaitan dengan pekerjaan, menulis surat lamaran dan CV dan bercakap-cakap dengan berbahasa Inggris rekan adalah kebutuhan yang paling penting dalam jangka kebutuhan pekerjaan.Â kata kunci: ESP, mahasiswa fisika, kebutuhan bahasa